TECHNICAL ANALYSIS OF SEA CUCUMBER CATCH AND PROCESSING ONBOARD FISHING VESSELS AT WEST COAST WATERS OF SUMATERA - Fani; Fis Purwangka; Budhi Hascaryo Iskandar (Jurnal Penelitian Perikanan Laut (Albacore), 2025)
Sea cucumbers are high value fishery commodities that play an important role in international trade. Despite their significant economic contribution, scientific information regarding the technical aspects of sea cucumber harvesting and onboard processing remains limited. This study aims to examine the technical practices of sea cucumber harvesting and onboard processing through a case study in the West Coast waters of Sumatra. The research was conducted in October 2025 in the waters of Tello Island, South Nias, using direct observation methods by participating in the entire operational sequence of sea cucumber harvesting and processing onboard fishing vessels. Primary data were collected through field observations and interviews with the vessel captain and crew members, while secondary data were obtained from fishing operation documents. The results indicate that the operational workflow of sea cucumber harvesting is systematically organized, encompassing preparation stages, compressor-assisted diving operations, and the regulation of divers’ working and resting periods. Onboard sea cucumber processing involves sequential stages of cleaning, boiling, soaking in saline solution, smoking, and drying, utilizing simple facilities and traditional methods. The technical workflows of harvesting and processing, as presented in tabular form, represent actual operational conditions in the field and provide an essential basis for understanding operational effectiveness, existing limitations, and the potential for sustainable development of sea cucumber fisheries. Key words: compressor diving, harvesting techniques, onboard processing techniques, sea cucumber